Whole Mount in situ Localization of miRNAs and mRNAs During Somatic Embryogenesis in Arabidopsis - Wójcik, Anna M.; Mosiolek, Magdalena; Karcz, Jagna; Nodine, Michael D.; Gaj, Małgorzata D. (Frontiers in Plant Science, 2018)
Somatic embryogenesis (SE) results from the transition of differentiated plant somatic cells into embryogenic cells that requires the extensive reprogramming of the somatic cell transcriptome. Commonly, the SE-involved genes are identified by analyzing the heterogeneous population of explant cells and thus, it is necessary to validate the expression of the candidate genes in the cells that are competent for embryogenic transition. Here, we optimized and implemented the whole mount in situ hybridization (WISH) method (Dastidar et al. 2016; Bleckmann and Dresselhaus, 2016) in order to analyze the spatiotemporal localization of miRNAs (miR156, miR166, miR390, miR167) and mRNAs such as WOX5 and PHABULOSA-target of miR165/166 during the SE that is induced in Arabidopsis explants. This study presents a detailed step-by-step description of the WISH procedure in which DIG-labeled LNA and RNA probes were used to detect miRNAs and mRNAs, respectively. The usefulness of the WISH in the functional analysis of the SE-involved regulatory pathways is demonstrated and the advantages of this method are highlighted: (1) the ability to analyze intact non-sectioned plant tissue; (ii) the specificity of transcript detection; (iii) the detection of miRNA and (iv) a semi-quantitative assessment of the RNA abundance.